Negative evidence for a role of APH1B T27I variant in Alzheimer's disease. (29th January 2020) - Zhang, Xulun; Zhang, Can; Prokopenko, Dmitry; Liang, Yingxia; Han, Weinong; Tanzi, Rudolph E; Sisodia, Sangram S
Abstract: γ-secretase is a macromolecular complex that catalyzes intramembranous hydrolysis of more than 100 membrane-bound substrates. The complex is composed of presenilin (PS1 or PS2), anterior pharynx defect-1 (APH-1), nicastrin (NCT) and PEN-2 and early-onset; autosomal dominant forms of Alzheimer's disease (AD) are caused by inheritance of mutations of PS. No mutations in genes encoding NCT, or PEN-2 have been identified to date that cause AD. In this regard, a large genetic meta-analysis of four cohorts consisting of more than 600 000 individuals identified a common missense variant, rs117618017 in the APH1B gene that results in a T27I mutation, as a novel genome-wide significant locus. In order to confirm the findings that rs117618017 is associated with risk of AD, we performed a genetic screen from deep whole genome sequencing of the large NIMH family-based Alzheimer's Disease (AD) dataset. In parallel, we sought to uncover potential molecular mechanism(s) by which APH-1B T27I might be associated with AD by generating stable HEK293 cell lines, wherein endogenous APH-1A and APH-1B expression was silenced and into which either the wild type APH-1B or the APH-1B T27I variant was stably expressed. We then tested the impact of expressing either the wild type APH-1B or the APH-1B T27I variant on γ-secretase processing of human APP, the murine Notch derivative mNΔE and human neuregulin-1. We now report that we fail to confirm the association of rs1047552 with AD in our cohort and that cells expressing the APH-1B T27I variant show no discernable impact on the γ-secretase processing of established substrates compared with cells expressing wild-type APH-1B.